A single - center, retrospective observational study comparing the efficacy of empagliflozin and dapagliflozin as add-on therapy in type 2 diabetic patients - Hau, Nguyen Van Vy; Bang, Nguyen Van; Xuan, Nguyen Thi; Linh, Pham Nguyen Tuyen; Thoi, Nguyen Thi Ngoc; Trang, Vo Thanh; Trung, Phan Minh; Chi, Le Van; Thuy, Nguyen Hai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Objective: This study aimed to compare the efficacy of dapagliflozin and empagliflozin as add-on therapies for type 2 diabetes mellitus (T2DM) over 6 months in a real-world setting, focusing on key metabolic parameters. Methods: We conducted a single-center, retrospective observational study involving 74 T2DM patients receiving either dapagliflozin (10mg) or empagliflozin (25mg) as add-on therapy. Data from 843 patients’s electronic medical records were collected at the Center for Endocrinology and Diabetes, Da Nang Family Hospital, between May 2021 and June 2023. Baseline data and data from the 3rd and 6th months of treatment were analyzed using SPSS software (version 20.0). Statistical significance was set at p < 0.05. Results: The mean participant age was 58.8 years, with 54.1% females. Mean baseline HbA1c and fasting blood glucose were 8.18% and 9.1 mmol/L, respectively. After 6 months of SGLT2i treatment, both medications significantly improved glycemic control: HbA1c decreased from 8.18% to 7.3% (p < 0.05), and fasting plasma glucose dropped from 9.1 mmol/L to 7.4 mmol/L (p < 0.05). Systolic blood pressure also decreased significantly, from 130.7 mmHg to 126.5 mmHg (p < 0.05). Although a trend towards weight reduction (1.5 kg) was observed, it was not statistically significant (p > 0.05). Notably, empagliflozin led to a significantly greater decrease in fasting plasma glucose compared to dapagliflozin (p < 0.05). No other significant differences in metabolic parameters were observed between the groups at either 3 or 6 months. Conclusion: Both dapagliflozin and empagliflozin demonstrated significant efficacy as add-on therapies forT2DM patients, improving glycemic control, reducing blood pressure, and potentially promoting weight loss. While empagliflozin showed slightly better BMI, body weight and fasting plasma glucose reduction after 3 months, further research is needed to confirm this finding and explore underlying mechanisms.